The Wireless Acquisition Data System Simulator Design on Automatic Weather Monitoring Station - Siti Aminah; Asep Deni Mulyadi; Yuliadi Erdani (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2019)
The Wireless Acquisition Data System Simulator Design on Automatic Weather Monitoring Station is means of collecting, monitoring, and controlling some long distance subsystems. Automatic weather monitoring station is device for receiving data by a censor in use to gauge some weather parameters. In this Research we develop an automatic weather monitoring station design simulator by creating a subsystem in the form of prototype, using Digital Pin and Analog Pin from the microcontroller. Sensor characteristics are considered to measure several weather parameters. The principles of a system function are it will have to collect data from some subsystems to accommodate in a database, able to control and deliver instructions to the subsystem. The communication system makes the use of radio frequency by means of Frequency Shift Keying (FSK) method through Handy Talky (HT), picked out because advantages of lower power consumptions and long range of transmission. Additional advantages are, although catastrophes, data communication using HT allows to keep fast transmission. The transmission of data using HT media require a signal converter by which HT is operated by analogue signal (sound), while censor and microcontroller by digital signal and, therefore, Modulation and Demodulation techniques are necessary. The Modulation functions to convert digital signal into analogue, and just the opposite to the Demodulation, the Modulation and Demodulation processes is using IC TCM3105. The results of the trial suggest that system design has proper functions, the communication process in this system is two-ways communication, the process was fast working in either transmitter mode or receiver mode.